Ligand-induced DNA conformational changes in proflavine minor groove-bound complexes studied by molecular dynamics simulation - Miroshnychenko, K. V.; Shestopalova, A. V. (Biophysical Bulletin, 2019)
Background: Minor groove binding is a rate-limiting step in proflavine-DNA intercalation reaction. This step is believed also to be responsible for the sequence-dependent kinetics of proflavine binding to DNA. At the same time, most studies are focused on the final stage of the reaction – the intercalation complex, and there is a lack of data concerning the structure and stability of proflavine-DNA minor groove-bound complexes.Objectives: The objective of this study was to investigate the stability of proflavine minor groove-bound complexes with DNA oligonucleotides of different sequence by molecular dynamics simulation and to analyze the DNA conformational changes caused by the proflavine binding.Materials and methods: The molecular dynamics simulations of proflavine minor groove-bound complexes with poly(dA)·poly(dT) and poly(dCG)·poly(dCG) oligonucleotides of 30 bp length were done in program package AMBER12 with explicit water (SPC/E) and ions (NaCl 0.15 M) using force fields FF14SB for DNA and GAFF for ligand. The starting configurations of complexes were obtained by docking method in AutoDock 3.05. After multi-stage equilibration protocol, each system was simulated at T=300 K and p=1 bar for a 50 ns production phase. Then trajectories were post-processed in AMBERTools17 and VMD-1.9.3 packages.Results: Our simulations confirm that proflavine-DNA minor groove-bound complexes are stable in the 50 ns time range but there are some structural rearrangements in them with respect to the initial structures. The narrowing of the DNA minor groove is observed in the proflavine binding site. In proflavine-poly(dCG)·poly(dCG) complex it is more pronounced and is accompanied by the BI/BII transitions in DNA and the reorientation of ligand. In proflavine-poly(dA)·poly(dT) complex the specific intermolecular hydrogen bonds are formed, which are optimized by the changes in opening and propeller twisting of involved AT-base pairs. Complexes are stabilized by the van der Waals and hydrophobic interactions, which are more favorable in the proflavine-poly(dA)·poly(dT) complex.Conclusions: Our results show that the binding of proflavine to a minor groove of DNA induces the conformational changes in the DNA that are important for the resulting complex stability.